"I Know Myself Again, Which Makes Me Motivated for Life": Feasibility and Acceptability of Using Experience Sampling Methods With Trauma-Exposed Sexual Minority Women. - Scheer, Jillian R.; Cascalheira, Cory J.; Helminen, Emily C.; Shaw, Thomas J.; Schwarz, Aubriana A.; Jaipuriar, Virinca; Brisbin, Cal D.; Batchelder, Abigail W.; Sullivan, Tami P.; Jackson, Skyler D. (Journal of Interpersonal Violence, 2023)
Intensive longitudinal designs (e.g., experience sampling methods [ESMs]) hold promise for examining the dynamic interplay between daily adversity, coping strategies, and behavioral and mental health issues among marginalized populations. However, few studies have used intensive longitudinal designs with sexual minority women (SMW), an understudied and at-risk population. We assessed feasibility and acceptability of using once-daily, interval-contingent ESM with 161 trauma-exposed SMW (M = 29.1, SD = 7.57); 20.5% nonbinary; 32.3% queer; 52.2% people of color; 14.3% with annual incomes ≤$9,999; and 30.4% in Southern United States (U.S.). SMW completed one comprehensive online baseline assessment and once-daily brief online assessments for 14 days. Daily surveys assessed past-24-hour stressors, stress responses, and behavioral and mental health symptoms. At the end of the 14-day ESM period, SMW answered three open-ended questions about participating in this study and about research with SMW. Regarding feasibility, 151 participants (94.0%) initiated the post-baseline ESM study portion and 72 (45.0%) completed all 14 daily surveys. An average of 11.70 (median = 13, SD = 3.31) daily surveys (83.5%) were completed by those who initiated the ESM. ESM completion level varied by race/ethnicity and U.S. region. Qualitative acceptability data revealed several themes, namely that SMW (1) enjoyed participating and felt positively about the ESM experience, (2) felt supported to reflect on impacts of early and ongoing stressors, (3) appreciated the chance to self-reflect and challenge existing thought patterns and coping behaviors, (4) recognized their capacity to tolerate trauma-related distress, (5) recommended that researchers focus on SMW's diverse stressors and daily experiences, (6) wanted a rationale for providing sensitive information and more space to narrate their experiences, and (7) recognized the need for affirmative treatment and policies. Findings could inform modifications to ESM protocols to improve their feasibility and acceptability among trauma-exposed SMW and promote ongoing utility of this valuable method.